2017
DOI: 10.1002/psc.2953
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin – new perspectives of a potent peptide hormone

Abstract: Adrenomedullin (ADM) is a 52-amino acid multifunctional peptide, which belongs to the calcitonin gene-related peptide (CGRP) superfamily of vasoactive peptide hormones. ADM exhibits a significant vasodilatory potential and plays a key role in various regulatory mechanisms, predominantly in the cardiovascular and lymphatic system. It exerts its effects by activation of the calcitonin receptor-like receptor associated with one of the receptor activity-modifying proteins 2 or 3. ADM was first isolated from human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
81
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 228 publications
(385 reference statements)
0
81
0
4
Order By: Relevance
“…The combination of RAMP 2 or 3 with the calcitonin receptor‐like receptor (CRLR) confers specificity of the receptor for ADM, and thus both RAMPs and CRLR are key in ADM expression . While ADM was first discovered in pheochromocytoma originating from the adrenal medulla (hence the name ‘adrenomedullin’), further investigation showed that it was synthesized by many other tissues/cells, especially endothelial and vascular smooth muscle cells, and due to its small size (6 kDa) diffuses freely between blood and interstitium . By proteolytic fragmentation of the pro‐hormone (pro‐ADM), a glycine‐extended, inactive ADM is formed, which subsequently is enzymatically converted from ADM‐glycine to the biologically active ADM‐amide.…”
Section: Adrenomedullin: An Introductionmentioning
confidence: 99%
“…The combination of RAMP 2 or 3 with the calcitonin receptor‐like receptor (CRLR) confers specificity of the receptor for ADM, and thus both RAMPs and CRLR are key in ADM expression . While ADM was first discovered in pheochromocytoma originating from the adrenal medulla (hence the name ‘adrenomedullin’), further investigation showed that it was synthesized by many other tissues/cells, especially endothelial and vascular smooth muscle cells, and due to its small size (6 kDa) diffuses freely between blood and interstitium . By proteolytic fragmentation of the pro‐hormone (pro‐ADM), a glycine‐extended, inactive ADM is formed, which subsequently is enzymatically converted from ADM‐glycine to the biologically active ADM‐amide.…”
Section: Adrenomedullin: An Introductionmentioning
confidence: 99%
“…Adrenomedullin (ADM) is a peptide hormone consisting of 52 amino acids, which was discovered in 1993 as an isolate of pheochromocytoma tissue . It plays a pivotal regulatory role in various physiological processes, mostly but not exclusively associated with the cardiovascular system . Besides its strong vasodilative properties, it induces angiogenesis as well as lymphangiogenesis, contributes to fluid and electrolyte homeostasis, plays an important role during pregnancy, and possesses antimicrobial properties .…”
Section: Introductionmentioning
confidence: 99%
“…It plays a pivotal regulatory role in various physiological processes, mostly but not exclusively associated with the cardiovascular system . Besides its strong vasodilative properties, it induces angiogenesis as well as lymphangiogenesis, contributes to fluid and electrolyte homeostasis, plays an important role during pregnancy, and possesses antimicrobial properties . Furthermore, it has been shown that ADM is overexpressed in various cancer types, where it acts as a tumor survival factor .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since its discovery in 1993 by isolation from human pheochromocytoma tissue, av ariety of physiological implications have been identified. [2,3] ADM plays ac rucial role in the regulation of numerous cardiovascular processes, such as vasodilation,a ngiogenesis, lymph angiogenesis and the reduction of oxidative stress. [4] Furthermore, ADM gene expression was found to be upregulatedd uring pregnancy,b ut also in varioust umor cell lines and malignant tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Therefore, it is of increasingi mportance as an early-stage biomarker for variousd iseases and as ap otential therapeutic agent. [3,6] The peptides of the CGRP family are able to differentially activate subtypes of the class BGprotein-coupled receptor (GPCR)c alcitonin receptor-like receptor (CLR),w hich are formed by heterodimerization with one of three receptora ctivity-modifying proteins (RAMP 1, 2, or 3). [7] ADM signals primarily through the ADM-1 receptor (AM 1 R, CLR + RAMP2) and the ADM-2 receptor (AM 2 R, CLR + RAMP3), but is also able to activate the CGRP receptor( CGRPR, CLR + RAMP1) with decreased potency.…”
Section: Introductionmentioning
confidence: 99%